The Impact of Risk Management on the Dimensions of Project Management Among Small and Medium Enterprises in Iraq - Abdulhadi, Ali Raqee; Ariffin, Mohd Khairol Anuar Bin Mohd; Abdulsamad, Akram; Al-Zubaidi, Razi; Leman, Zulkiflle B.; Ahmad, Siti Azfanizam binti (Advances in Social Sciences Research Journal, 2022)
The present study investigates the relationship between risk management and project management among Iraq construction SMEs. The current research is focused on risk management as a unidimensional, while project management was taken as multi-dimensional by using its four main components, which are project scope, project timelines, project benefits, and project quality. Data were gathered from the employees who are working in construction SMEs in Iraq. 251 questionnaires were received and analyzed by using SPSS and smart PLS-SEM to measure the research model fit and examine the hypothesis whether accepted or not within the study context. The model measurement and structural equation model test indicated that all four main hypotheses were accepted, which means that risk management has a positive impact on the four main components of project management in the construction field in Iraq SMEs. Also, the theoretical and managerial implications of this research were then discussed at the end of this article.